ANALYZING FACTOR INFLUENCE RESTAURANT AWARENESS TO PAY RESTAURANT TAX IN MALANG - Prananda, Harya; Adam, Helmy (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research used to know about the restaurant owner compliance paying tax. This research uses descriptive and quantitative method within restaurant sample in Malang, to calculating the restaurant owner compliance paying tax. To calculate the level of compliance paying restaurant tax using four factor like tax law, counseling, sanction and awareness to pay the tax. The result of this research is the compliance paying restaurant influence in two significant factor like tax law and awareness restaurant owner to compliance paying tax. In the other side counseling and sanction of tax didn’t significant factor to compliance paying tax Keywords: Tax, compliance paying tax, awareness paying tax